Nurses' perspectives and experience in caring for patients undergoing hemodialysis at Benjamin Mkapa hospital in Dodoma, Tanzania: A qualitative study. - Stephania Mbunda; Neema E Mawi; Masunga K Iseselo (PLoS ONE)
Background Caring for patients undergoing hemodialysis is a challenge for nurses. Poor quality of care in hemodialysis is reported to have a significant contribution to the high mortality rate among patients. Improving the health outcomes of the patient requires an in-depth exploration of the perspectives and views of nurses working in the hemodialysis unit. However, there is a paucity of information regarding the perspectives and experiences of nurses working in Hemodialysis units, particularly in resource-constrained countries like Tanzania. This study aimed to explore the perspectives and experiences of nurses caring for patients undergoing hemodialysis. Materials and methods An explorative qualitative study was conducted among nurses working in Hemodialysis units at Benjamin Mkapa Hospital in Dodoma, Tanzania. A purposive sampling method was used to select the participants. Ten in-depth interviews were conducted using a semi-structured interview guide and an audio recorder as the main data collection tools. A thematic analysis approach was used to analyze the data. Findings Three themes and the associated subthemes emerged from this study. 1) Conducive environments for the provision of nursing care 2) Challenges affecting hemodialysis care, and 3) Strategies for improving hemodialysis care. A good nurse-patient relationship, financial incentives, and availability of equipment facilitate the provision of care among patients. Treatment costs, problems in adhering to dialysis prescriptions, and staff shortages were the challenges affecting hemodialysis care. On the other hand, increasing dialysis centres, training nurses, and free health insurance coverage were strategies for improving hemodialysis care. Conclusion The findings highlighted several key aspects related to the perspectives and experiences of providing nursing care for patients undergoing hemodialysis. The conducive working environment, coupled with financial incentives, is an important factor in improving nurses' care for patients undergoing hemodialysis. However, the high costs related to the utilization of hemodialysis services are the challenge to achieving better outcomes.